NEUROSCIENCE-BASED BEGINNING READING LEARNING ON PHONOLOGICAL ABILITY AND READING COMPREHENSION - Eka Kurnia; Devi Afriyuni Yonanda; Kartimi; Ryan Dwi Puspita (Jurnal Cakrawala Pendas, 2025)
This study aims to analyze the effectiveness of early reading learning based on neuroscience principles on the phonological abilities and early reading comprehension of first grade elementary school students. In the context of education, reading is a very important basic skill, especially in the early stages of child development. Good reading skills not only affect students' academic achievement but also contribute to their cognitive and social development. Therefore, it is important to explore learning methods that can improve reading skills, especially for students in grade I. The method used in this study is the Systematic Literature Review (SLR), which is a systematic approach to collecting and analyzing data from various sources. In this case, this study collects information from academic journals and current research articles that are relevant to the topic of reading learning and neuroscience. Through SLR, researchers can evaluate and synthesize findings from various studies, resulting in a more comprehensive understanding of the effectiveness of neuroscience-based approaches in reading learning. The results of the analysis show that neuroscience-based approaches not only improve students' phonological abilities but also contribute significantly to early reading comprehension. Phonological abilities, which include phoneme awareness, the ability to recognize and manipulate sounds in words, are an important foundation for reading learning. Research shows that students who engage in learning designed based on neuroscience principles show significant improvements in their phonological abilities. For example, methods involving sound games and interactive activities have been shown to be effective in helping students understand the relationship between sounds and letters.